Three toxic gases meet in the mitochondria - Decreau, Richard A.; Collman, James P. (Frontiers in Physiology, 2015)
The rationale of the study was two-fold: (i) develop a functional synthetic model of the Cytochrome c oxidase (CcO) active site, (ii) use it as a convenient tool to understand or predict the outcome of the reaction of CcO with ligands (physiologically relevant gases and other ligands). At physiological pH and potential, the model catalyzes the 4-electron reduction of oxygen. This model was immobilized on self-assembled-monolayer (SAM) modified electrode. During catalytic oxygen reduction, electron delivery through SAMs is rate limiting, similar to the situation in CcO. This model contains all three redox-active components in CcO's active site, which are required to minimize the production of partially-reduced-oxygen-species (PROS): Fe-heme (“heme a3”) in a myoglobin-like model fitted with a proximal imidazole ligand, and a distal tris-imidazole Copper (“CuB”) complex, where one imidazole is cross-linked to a phenol (mimicking “Tyr244”). This functional CcO model demonstrates how CcO itself might tolerate the hormone NO (which diffuses through the mitochondria). It is proposed that CuB delivers superoxide to NO bound to Fe-heme forming peroxynitrite, then nitrate that diffuses away. Another toxic gas, H2S, has exceptional biological effects: at ~80 ppm, H2S induces a state similar to hibernation in mice, lowering the animal's temperature and slowing respiration. Using our functional CcO model, we have demonstrated that at the same concentration range H2S can reversibly inhibit catalytic oxygen reduction. Such a reversible catalytic process on the model was also demonstrated with an organic compound, tetrazole (TZ). Following studies showed that TZ reversibly inhibits respiration in isolated mitochondria, and induces deactivation of platelets, a mitochondria-rich key component of blood coagulation. Hence, this program is a rare example illustrating the use of a functional model to understand and predict physiologically important reactions at the active site of CcO.